Analysis of specific cognitive ability characteristics of Chinese women curling athletes - Zhang, S.-Z (Advanced Materials Research, 2014)
To provide cognitive psychological evidences in material selection, training and competition for athletes in Chinese women curling, methods include document literature, expert interview, experimental measurement and mathematical statics are employed. Athletes in National women curling team and provincial curling team of Heilongjiang are the main object of this study. In terms of cognitive ability, systematic research of women curling athletes` psychological feature are conducted. Research results show that, women curling athletes at different level have very significant differences in index of attention concentration and significant differences in time perception, depth perception and movement memory; athletes of different training time have very significant differences in index of wrist stability, and female curling athletes are tend to be inferior to their male counterparts in attention focusing.